2014
DOI: 10.1007/s40071-014-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Mass mortality event of the blood cockle, Anadara granosa, in aquaculture ground along Selangor coast, Peninsular Malaysia

Abstract: A mass mortality event of blood cockles, Anadara granosa, occurred in aquaculture ground in Selangor in mid-February 2012. To identify factors contributing to this event, we estimated the changes in survival rate and population density of the blood cockles using data from field surveys carried out in late-January and mid-March, 2012. In addition, blood cockle samples were used for histological observation of various tissues with a light microscope. Furthermore, we examined the environmental factors that seemed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
3
12
1
3
Order By: Relevance
“…The input of organic matter into the sediment can lead to a series of changes in physical and chemical parameters, which in turn have both direct and indirect effects on the benthic fauna communities as well as the growth and mortality of cockle in this area. This is in accordance with the previous studies of Yurimoto, Kassim, Fuseya, & Man, 2014;Ramli, Hassan, &Ramachandran, 2014 andMirsadeghi, Zakaria, Yap, &Gobas, 2013;Davenport & Wong, 1986. Yurimoto et al, (2014 reported that a mass mortality event of the blood cockle A. granosa in aquaculture ground in 2012 may have resulted from an impact of freshwater flooding from rivers on the aquaculture ground such as low-salinity environments and low food availability.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The input of organic matter into the sediment can lead to a series of changes in physical and chemical parameters, which in turn have both direct and indirect effects on the benthic fauna communities as well as the growth and mortality of cockle in this area. This is in accordance with the previous studies of Yurimoto, Kassim, Fuseya, & Man, 2014;Ramli, Hassan, &Ramachandran, 2014 andMirsadeghi, Zakaria, Yap, &Gobas, 2013;Davenport & Wong, 1986. Yurimoto et al, (2014 reported that a mass mortality event of the blood cockle A. granosa in aquaculture ground in 2012 may have resulted from an impact of freshwater flooding from rivers on the aquaculture ground such as low-salinity environments and low food availability.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with the previous studies of Yurimoto, Kassim, Fuseya, & Man, ; Ramli, Hassan, & Ramachandran, and Mirsadeghi, Zakaria, Yap, & Gobas, ; Davenport & Wong, . Yurimoto et al, () reported that a mass mortality event of the blood cockle A. granosa in aquaculture ground in 2012 may have resulted from an impact of freshwater flooding from rivers on the aquaculture ground such as low‐salinity environments and low food availability. However, blood cockle normally exhibit resistance to low salinity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sementara itu, berdasarkan kandungan nutrien, kerang darah mengandung protein 18,91%, lemak 2,66%, karbohidrat 4,16%, serta beberapa komponen mineral lainnya yang berpotensi sebagai antioksidan (Chi et al 2015;Sukina et al 2020) Kerang darah umumnya terdistribusi pada daerah pasang surut dengan komposisi sedimen berupa lumpur dan lumpur berpasir (Joni et al 2019). Kerang darah mampu berkembang dengan baik pada kisaran salinitas mulai dari 26 sampai 31 ppt (Yurimoto et al 2014). Di samping itu, parameter fisika-kimiawi air dan sedimen lainnya, seperti kandungan C-organik serta polutan juga ikut memengaruhi kelangsungan hidup pertumbuhan kerang darah (Hashim et al 2020;Mohamat-Yusuff et al 2020;Yurimoto et al 2021).…”
Section: Pendahuluanunclassified
“…Sejauh ini, kajian lebih dalam terkait variasi genetik, pengaruh ketersediaan makanan, dan kompetisi dalam ekosistem yang dihuni oleh kerang darah, khususnya dari lokasi penelitian masih belum ditemukan. Yurimoto et al (2014) Parapenaeopsis stylifera) untuk mendapatkan jenis makanan yang sama berupa mikroalga dan detritus.…”
Section: Sebaran Kelas Panjang Dan Bobotunclassified